Current Status of the Algae Production Industry in Europe: An Emerging Sector of the Blue Bioeconomy - Araújo, Rita; Vázquez Calderón, Fatima; Sánchez López, Javier; Azevedo, Isabel Costa; Bruhn, Annette; Fluch, Silvia; Garcia Tasende, Manuel; Ghaderiardakani, Fatemeh; Ilmjärv, Tanel; Laurans, Martial; Mac Monagail, Micheal; Mangini, Silvio; et al. (Frontiers in Marine Science, 2021)
The EU Bioeconomy Strategy aims to support the sustainable growth and development of the EU bio-based sectors while creating jobs, innovation and services. Despite the recognized potential of the algae biomass value chain, significant knowledge gaps still exist regarding the dimension, capability, organization and structure of the algae production in Europe. This study presents and analyses the results of a comprehensive mapping and detailed characterization of the algae production at the European scale, encompassing macroalgae, microalgae, and the cyanobacteria Spirulina. This work mapped 447 algae and Spirulina production units spread between 23 countries, which represents an important addition to the reported number of algae producing countries. More than 50% of these companies produce microalgae and/or Spirulina. Macroalgae production is still depending on harvesting from wild stocks (68% of the macroalgae producing units) but macroalgae aquaculture (land-based and at sea) is developing in several countries in Europe currently representing 32% of the macroalgae production units. France, Ireland, and Spain are the top 3 countries in number of macroalgae production units while Germany, Spain, and Italy stand for the top 3 for microalgae. Spirulina producers are predominantly located in France, Italy, Germany, and Spain. Algae and Spirulina biomass is directed primarily for food and food-related applications including the extraction of high-value products for food supplements and nutraceuticals. Algae production in Europe remains limited by a series of technological, regulatory and market-related barriers. Yet, the results of this study emphasize that the European algae sector has a considerable potential for sustainable development as long as the acknowledged economic, social and environmental challenges are addressed.